Dose–response relationships between mouse allergen exposure and asthma morbidity among urban children and adolescents. (23rd November 2012) - Torjusen, E. N.; Diette, G. B.; Breysse, P. N.; Curtin‐Brosnan, J.; Aloe, C.; Matsui, E. C.
Abstract Home mouse allergen exposure is associated with asthma morbidity, but little is known about the shape of the dose–response relationship or the relevance of location of exposure within the home. Asthma outcome and allergen exposure data were collected every 3 months for 1 year in 150 urban children with asthma. Participants were stratified by mouse sensitization, and relationships between continuous measures of mouse allergen exposure and outcomes of interest were analyzed. Every tenfold increase in the bed mouse allergen level was associated with an 87% increase in the odds of any asthma‐related health care use among mouse‐sensitized [Odds Ratio (95% CI): 1.87 (1.21–2.88)], but not non‐mouse‐sensitized participants. Similar relationships were observed for emergency department visit and unscheduled doctor visit among mouse‐sensitized participants. Kitchen floor and bedroom air mouse allergen concentrations were also associated with greater odds of asthma‐related healthcare utilization; however, the magnitude of the association was less than that observed for bed mouse allergen concentrations. In this population of urban children with asthma, there is a linear dose–response relationship between mouse allergen concentrations and asthma morbidity among mouse‐sensitized asthmatics. Bed and bedroom air mouse allergen exposure compartments may have a greater impact on asthma morbidity than other compartments.